2016
DOI: 10.1002/smj.2478
|View full text |Cite
|
Sign up to set email alerts
|

The throne vs. the kingdom: Founder control and value creation in startups

Abstract: Research summary: Does the degree to which founders keep control of their startups affect company value? I argue that founders face a “control dilemma” in which a startup's resource dependence drives a wedge between the startup's value and the founder's ability to retain control of decision making. I develop hypotheses about this tradeoff and test the hypotheses on a unique dataset of 6,130 American startups. I find that startups in which the founder is still in control of the board of directors and/or the CEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 134 publications
(200 reference statements)
5
148
0
3
Order By: Relevance
“…To our knowledge, our study is the first to depict founder‐CEOs' strategies to secure control after IPO as a multi‐stage process with potentially positive net outcomes. Finally, we extend research initiated by Wasserman (, ), which depicts the tradeoff between founder's motivation for (a) financial gains and (b) control as mutually exclusive rich versus king alternatives. For instance, Wasserman () showed that after having a positive effect on firm value during the early stages of startup growth, founders who continue to control their private startups increasingly destroy firm value on average.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…To our knowledge, our study is the first to depict founder‐CEOs' strategies to secure control after IPO as a multi‐stage process with potentially positive net outcomes. Finally, we extend research initiated by Wasserman (, ), which depicts the tradeoff between founder's motivation for (a) financial gains and (b) control as mutually exclusive rich versus king alternatives. For instance, Wasserman () showed that after having a positive effect on firm value during the early stages of startup growth, founders who continue to control their private startups increasingly destroy firm value on average.…”
Section: Introductionmentioning
confidence: 63%
“…Our study is among the few to investigate the net effects of founder‐CEOs' strategies to maintain control post‐IPO in a multi‐stage process. Finally, and more generally, we challenge previous work suggesting that founders have to sacrifice control to increase firm value by illustrating a context where rich versus king alternatives might occur simultaneously (Wasserman, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, there is a trade‐off between the resources that board members provide and the power over the venture's direction that must be relinquished to them (Pfeffer & Salancik, ). For example, in a survey‐based study, Wasserman () examines the entrepreneur's ex ante choice between gaining the resources needed for growth versus retaining control (including of the board). He finds that if entrepreneurs choose control, then venture performance suffers.…”
Section: Literature On Venture Boards: Recent and Theory‐based Studiesmentioning
confidence: 99%
“…Relying on a sample of more than 2,000 firms that went public from 1997–2013, we examine the performance implications of team structure for founder and nonfounder firms. Overall, our results suggest that founders' tendency to centralize decision‐making (Wasserman, ) might lead them to rely more on their own judgment and less on their team . As a result, founders centralize decisions that enable them to pursue their objectives, but by so doing they sacrifice the performance benefits of the TMT's expertise.…”
Section: Introductionmentioning
confidence: 99%